Análisis de la dinámica y distribución espacial-actual y futura de cinco especies en Sistemas Agroforestales de la Región Sur del Ecuador bajo escenarios de cambio climático - Zhingre Jiménez, Willam Alexander (2024)
Currently, biodiversity plays a fundamental role in the functioning of ecosystems; however, climate change is causing alterations in the distribution of species, the loss of flora and fauna, as well as the deterioration of ecosystems and a decrease in environmental services. In Ecuador, the impacts of climate change are evident, affecting the country's population, infrastructure and production, which represents a vulnerability in priority sectors such as agriculture in the southern region of Ecuador. The present research is aimed to determine the current and future potential distribution of five species Vachellia macracantha, Ochroma pyramidale, Inga edulis, Myrsine andina and Pouteria sapota which are part of agroforestry systems in the southern region of Ecuador under scenarios of the fifth report (AR5) of the Intergovernmental Panel on Climate Change (IPCC), A compilation of observations of each of the species distributed in the southern region of Ecuador was carried out and filtered using the statistical package Biomod2 in RStudio, which used two jackknife statistical tests and the variance inflation factor (VIF) which determined the multicollinearity among the variables and allowed selecting the explanatory variables for the final assembly, which were evaluated by means of the Real Skill Statistical Test (TSS) and Receiver Operating Characteristic (ROC) that allowed to select the models that exceeded 0.8 of predictive performance and which were projected to the year 2030 2050 and 2080 respectively for each species concluding that the five species show persistence in both climate scenarios, experiencing fluctuations between gains and losses under environmental pressures, from the RCP 2.6 and RCP 8.5 scenarios, showing a variable adaptability, however the capacity of the species to develop new potential distribution areas is limited by their environmental conditions, thus revealing their vulnerability to climate change.